Liber, Augustus and Mark Antony - Serignolli, Lya (2024)
Libertas was an essential issue in Roman politics, connected to the beginnings of the Republic; and Liber was a divinity that corresponded to this aspect from different perspectives. The role of Liber as liberator was as old in Rome as the legends of the founders of the Republic, who were called liberators for their participation in the expulsion of the kings. Liber and libertas, especially in politics, were deeply rooted in the roman mind, and political leaders found it interesting to establish this connection. Between the forties and the thirties BC, several political leaders adopted divinities as patrons and models: Mark Antony, Dionysus and Hercules; and Octavian, at first, Apollo, and then Liber, that was convenient for his association with Alexander, the Great (as a symbol of the conquest of the East), as well as for his role as the italic god of vegetation and wine, connected to the old republican values. In the context of civil war, the struggle for power was presented in poetry as a confrontation between divine models. Taking advantage of Bacchus’paradoxical character, the Augustan poets associated his role as a deified hero, symbol of triumph and civilizing power to Augustus, reserving to Mark Antony his darkest aspects, such as drunkenness and excessive luxury. This article analyses how Horace contributes to the assimilation of Liber to the Augustan repertoire, in a moment of profound political transformations in Rome.